NHC-catalyzed atropoenantioselective synthesis of axially chiral biaryl amino alcohols via a cooperative strategy - Gongming Yang (Nature Portfolio, 2019)
Axially chiral biaryl amino-alcohols play a pivotal role in organic synthesis and drug discovery. Here, the authors report a cooperative strategy consisting of desymmetrization followed by kinetic resolution to deliver non-classical NOBIN derivatives in high yields and enantioselectivity via NHC catalysis.